PENERAPAN METODE PROBLEM BASE LEARNING DALAM MATAKULIAH BAHASA INDONESIA - Emmy Renoat (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2022)
This study contains an analysis of the application of the problem base learning method. This type of research is quantititave, namely a (quasi-experiment) with a research design of Nonequivalent control group design. This study uses data collection techniques in the from of test, observation and documentation. Data analysis in this study is data nalysis rerlated to understanding the concept of Indonesian Language Education. The result of quantitative description analysis show that the average value of student abilities who are taught using the Problem Based learning Model is 80.29% while the average value of stundents ablilities who are taught using convetional learning models is 74.375%. Problem Based Learning has a better effect than conventional learning models on stundents abilities (learning outcomes).